PENGARUH PENGGUNAAN MODEL COOPERATIVE LEARNING TIPE STUDENT FACILITATOR AND EXPLAINING (SFE) TERHADAP HASIL BELAJAR IPS TERPADU SISWA KELAS VII NEGERI 7 METRO - Atik Diana Kholisah; Wakijo Wakijo (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2018)
Based on the result of pre survey in SMP N 7 Metro, that is to be presented problem in this research namely: “There are many students at the VII grade that was not successful yet in their integrated social sciences learning outcomes at the odd semester SMP Negeri 7 Metro in academic year 2017/2018”. Based on the problem above, the problem formulation in this research is: Is there any influence of using Cooperative Learning Model Type Student Facilitator and Explaining (SFE) toward the Integrated Social Sciences Learning Outcomes of the students at the VII grade even semester SMP Negeri 7 Metro in Academic Year 2017/2018?. Based on the result of research data analysis used simple linier regression formula, it was found that a = b = . So, Ŷ = a + bXis . Then, it proved that there is a positive influence of using Cooperative Learning Model Type Student Facilitator and Explaining (SFE) toward the Integrated Social Sciences Learning Outcomes in SMP Negeri 7 Metro in Academic Year 2017/2018. It was proved by the calculation of data analysis that showed tobserved was higher than ttable (thitung>ttabel) in significance level of 5% was3,08> 1,71and in significance level of 1% was3,08>2,48. Therefore, the hypothesis is accepted that means there is a positive influence of using Cooperative Learning Model Type Student Facilitator and Explaining (SFE) toward the Integrated Social Sciences Learning Outcomes in SMP Negeri 7. Keywords: Learning Model Type Student Facilitator and Explaining (SFE), Learning Outcomes